Effect of Residents' Previous Laparoscopic Surgery Experience on Initial Robotic Suturing Experience. (2nd September 2012) - Kilic, Gokhan Sami; Walsh, Teresa M.; Borahay, Mostafa; Zeybek, Burak; Wen, Michael; Breitkopf, Daniel
Abstract : Objective . To assess the impact of gynecology residents' previous laparoscopic experience on the learning curve of robotic suturing techniques and the value of initial structured teaching in dry lab prior to surgery. Methods . Thirteen gynecology residents with no previous robotic surgery experience were divided into Group 1, consisting of residents with 2 or fewer laparoscopic experiences, and Group 2, consisting of residents with 3 or more laparoscopic experiences. Group 1 had a dry-laboratory training in suturing prior to their initial experience in the operating room. Results . For all residents, it took on average 382 ± 159 seconds for laparoscopic suturing and 326 ± 196 seconds for robotic suturing (P = 0.12 ). Residents in Group 1 had a lower mean suture time than residents in Group 2 for laparoscopic suturing (P = 0.009 ). The residents in Group 2, however, had a lower mean suture time on the robot compared to Group 1 (P = 0.5 ). Conclusion . Residents with previous laparoscopic suturing experience may gain more from a robotic surgery experience than those with limited laparoscopic surgery experience. In addition, dry lab training is more efficient than hands-on training in the initial phase of teaching for both laparoscopic and robotic suturing skills.